Estimations of the Jacking Forces of Large-Sized Rectangular Jacking Pipes Based on a Displacement Control Method - Zun-Qun Xiao (Hindawi Limited, 2021)
In the present study, based on previous research results, a finite element method that considered the grouting pressure and displacement control of the tube-soil side friction coefficients was established for the purpose of estimating the jacking forces of large sections of rectangular pipe jacking. Furthermore, the pipe jacking project of Zhong-Zhou Avenue was taken as an example in this study, in which the rectangular pipe jacking models A1 and B1 under silty clay geological conditions were established. The two estimation models were verified using the pipe jacking cases A2 and B2, respectively. The estimation model can effectively estimate the jacking force, and the rectangular jacking force is distributed as a logarithmic function with the jacking distance. The shallow buried rectangular pipe jacking has some common characteristics in buried depth, grouting pressure, the length-width ratio of outer diameter, construction geological conditions, and so on. The main independent factors that affect the jacking force are the buried depth and the outer perimeter of the jacking pipe. Based on the numerical model of case A1 and case B1, the logarithmic functions of jacking force of case A1 and case B1 with jacking distance were obtained by changing the buried depth. The calculation formula of the jacking force can reflect the variation law of the jacking force to some extent.